Effects of domestic violence on antenatal depression: meta-analysis - Dinda Anindita Salsabilla; Maya Ayu Riestiyowati; Tyas Aisyah Putri; Norayuni Mohd Ismail (Universitas Ahmad Dahlan, 2023)
Antenatal depression or depression in pregnant women is influenced by various factors, one of which is the stressor of the social life of the household life, such as domestic violence. Domestic abuse during pregnancy has a negative impact on the mother's health as well as the newborn's and the child's development. The purpose of this study is to determine how much domestic violence affects antenatal depression. This study uses a meta-analytic study design from articles published from 2008 to 2022 using the Google Scholar, PubMed, Springer Link, and ScienceDirect databases. Articles are collected for 2 months by keywords (“Intimate Partner Violence” OR “IPV” OR “Domestic Violence”) AND “Antenatal Depression” OR “Antepartum Depression” AND (“adjusted odds ratio” OR “multivariable”). The articles used are articles that meet the inclusion and exclusion criteria. There were 14 articles from 3 continents namely Asia, Africa, and North America with cross sectional and cohort study designs. Cross-sectional meta-analysis shows that domestic violence can increase the incidence of antenatal depression by 3.97 times compared by not experiencing domestic violence (aOR= 3.97; 95% CI= 2.44 to 6.47; p<0.001). Meanwhile, the cohort study showed that domestic violence can increase the incidence of antenatal depression by 2.58 times compared to not experiencing domestic violence (aOR= 2.58; 95% CI= 2.06 to 3.23; p<0.001). Total heterogeneity shows I2 = 81%, such that it can be said that the data distribution is heterogeneous (random effect model). Domestic violence can increase the incidence of antenatal depression.